2018
DOI: 10.1093/nar/gky086
|View full text |Cite
|
Sign up to set email alerts
|

Structurally distinct Mre11 domains mediate MRX functions in resection, end-tethering and DNA damage resistance

Abstract: Sae2 cooperates with the Mre11–Rad50-Xrs2 (MRX) complex to initiate resection of DNA double-strand breaks (DSBs) and to maintain the DSB ends in close proximity to allow their repair. How these diverse MRX-Sae2 functions contribute to DNA damage resistance is not known. Here, we describe mre11 alleles that suppress the hypersensitivity of sae2Δ cells to genotoxic agents. By assessing the impact of these mutations at the cellular and structural levels, we found that all the mre11 alleles that restore sae2Δ resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 73 publications
2
40
1
Order By: Relevance
“…Here, we show that the presence of the Mre11-R10T mutant variant, which bypasses Sae2 function in DNA damage resistance, causes a more efficient DSB end resection compared to wild-type Mre11. Unlike previously reported Mre11 mutant variants that suppress the DNA damage hypersensitivity and/or the resection defects of sae2Δ cells by potentiating the Sgs1-Dna2 resection activity through a lowering of MRX association with DSBs (Chen et al, 2015;Puddu et al, 2015;Cassani et al, 2018), the enhanced DSB resection in the presence of Mre11-R10T depends mainly on Exo1.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…Here, we show that the presence of the Mre11-R10T mutant variant, which bypasses Sae2 function in DNA damage resistance, causes a more efficient DSB end resection compared to wild-type Mre11. Unlike previously reported Mre11 mutant variants that suppress the DNA damage hypersensitivity and/or the resection defects of sae2Δ cells by potentiating the Sgs1-Dna2 resection activity through a lowering of MRX association with DSBs (Chen et al, 2015;Puddu et al, 2015;Cassani et al, 2018), the enhanced DSB resection in the presence of Mre11-R10T depends mainly on Exo1.…”
Section: Discussioncontrasting
confidence: 77%
“…Analysis of a structural alignment of the different structures available for Mre11 orthologs (Cassani et al , ) revealed that the positions corresponding to the R10 residue were highly conserved (Fig A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations